The effects of radical prostatectomy on gay and bisexual men's mental health, sexual identity and relationships: qualitative results from the restore study. Issue 4 (1st October 2016) - Rosser, B.R. Simon; Capistrant, Benjamin; Torres, Beatriz; Konety, Badrinath; Merengwa, Enyinnaya; Mitteldorf, Darryl; West, William
ABSTRACT: The effect of prostate cancer treatment in gay and bisexual men is an under-researched area. In 2015, we conducted in-depth telephone interviews with 19 gay and bisexual men who had undergone radical prostatectomies. Across the respondents' five emotional themes emerged: (1) shock at the diagnosis, (2) a reactive, self-reported "depression", (3) sex-specific situational anxiety, (4) a sense of grief, and, (5) an enduring loss of sexual confidence. Identity challenges included loss of a sense of maleness and manhood, changes in strength of sexual orientation, role-in-sex identity, and immersion into sexual sub-cultures. Relationship challenges identified included disclosing the sexual effects of treatment to partners, loss of partners, and re-negotiation of sexual exclusivity. Most to all of these effects stem from sexual changes. To mitigate these negative effects of radical prostatectomy, and to address health disparities n outcomes observed in gay and bisexual men, all these challenges need to be considered in any tailored rehabilitation program for gay and bisexual men.